Sculpting infant soothability: the role of prenatal SSRI antidepressant exposure and neonatal SLC6A4 methylation status. Issue 6 (2nd June 2016) - Gartstein, Maria A.; Hookenson, Kaia V.; Brain, Ursula; Devlin, Angela M.; Grunau, Ruth E.; Oberlander, Tim F.
Abstract: The role of prenatal Selective Serotonin Reuptake Inhibitor (SSRI) exposure and SLC6A4 promoter methylation status in shaping soothability at 3 and 6 months of age, for infants exposed to antidepressant medication prenatally ( n  = 46) and those not exposed ( n  = 69) was investigated. SSRI exposure status and duration of exposure (number of days) were examined along with neonatal methylation status at mean CpG 9, 10 and via factor analysis across 10 CpG sites yielding PC1 (CpGs sites: 3, 4, 5, 7) and PC2 (CpG 1, 8). Analyses revealed interactions for methylation markers and SSRI exposure variables. A significant interaction between SSRI exposure and mean SLC6A4 methylation at CpG 9, 10 and separately for PC1 emerged, controlling for multiple birth/medical and background covariates (e.g., Apgar scores, maternal education). Increased neonatal methylation status was associated with increased soothability changes from 3 to 6 months among infants prenatally exposed to SSRIs.